Halal kitchen rating system - Othman, Rashidi; Hashim, Khairusy Syakirin Has-Yun; Mahamod, Lukman Hakim; Abdul Aziz, Azurah (2018)
Halal Kitchen Rating System uses a rating score card method that rates all the major aspects of a kitchen operation and activities, and accredits the kitchen based on the score achieved in the form of number of stars. Halal Kitchen Rating System is carried out in 3 stages of the kitchen: • Design • Construction • Operation and maintenance Halal Kitchen Rating System is focusing on items such as: 1. General items 2. Materials 3. Premise 4. Process 5. Human resource 6. Innovation Every items above will be rated according to the points given based on the priority.